-2x+13=10-2x

Simple and best practice solution for -2x+13=10-2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2x+13=10-2x equation:


Simplifying
-2x + 13 = 10 + -2x

Reorder the terms:
13 + -2x = 10 + -2x

Add '2x' to each side of the equation.
13 + -2x + 2x = 10 + -2x + 2x

Combine like terms: -2x + 2x = 0
13 + 0 = 10 + -2x + 2x
13 = 10 + -2x + 2x

Combine like terms: -2x + 2x = 0
13 = 10 + 0
13 = 10

Solving
13 = 10

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| -9=x+(-19) | | 7y-2=19y+82 | | 10x-(6x-5)=41 | | 4x+5=2x+1 | | 2(2-3n)=[5n-(4-n)] | | x/3*8=3 | | 3m+8m=9m+m | | 3(2x-1)+4(x+3)=5(2-1)+4(3x-1) | | 3x*6=48 | | 2x=32-x | | 3(x-3)=7(x-2)-3 | | 2x-3(x-4)=8x-(5x-3) | | 2x^2-14x+9=0 | | +6v-v=7 | | x^2+6=11x | | -8x+4+2x=-10x+24 | | -n-5n=12 | | 2(2x+5)+5(x-7)= | | -10y+5=-5(2y-1) | | 2(2x-1)-6(1-2x)=2(4x-5) | | X^4-81=o | | 2(1-5x)=(5x-1) | | x-4+2=3 | | z/4-z/3-z/8=2 | | 3n-5+4n=16 | | -2m+6+6=16 | | 448=-16p | | 12x-9x^2=3 | | 36x^2-48x+16=0 | | 6-3= | | 6x^3-3x^2-2x+1=0 | | x+9=(x+9)(x+9)+7(x+9)-8 |

Equations solver categories